Direct Interactions With Cancer-Associated Fibroblasts Lead to Enhanced Pancreatic Cancer Stem Cell Function. Issue 3 (March 2019) - Begum, Asma; McMillan, Ross H.; Chang, Yu-Tai; Penchev, Vesselin R.; Rajeshkumar, N.V.; Maitra, Anirban; Goggins, Michael G.; Eshelman, James R.; Wolfgang, Christopher L.; Rasheed, Zeshaan A.; Matsui, William
Abstract : Objective: Cancer-associated fibroblasts (CAFs) play an important role in the progression of pancreatic ductal adenocarcinoma (PDAC) by promoting tumor cell migration and drug resistance. We determined the impact of CAFs on PDAC cancer stem cells (CSCs). Methods: Fibroblast cell lines from patients' tumors were cocultured with PDAC cells and examined for clonogenic growth and self-renewal using colony-forming assays and migration in vitro. Changes in the frequency of CSCs was determined by flow cytometry. The effect of integrin–focal adhesion kinase (FAK) signaling on CAF-mediated clonogenic growth was evaluated using short hairpin RNAs against β1 integrin and FAK as well as a small-molecule FAK inhibitor. Results: Cancer-associated fibroblasts enhanced PDAC clonogenic growth, self-renewal, and migration that was associated with an increase in the frequency of CSCs. These fibroblast cells were activated by PDAC cells and increased collagen synthesis resulting in FAK activation in PDAC cells. Knockdown of β1-integrin and FAK or the inhibition of FAK kinase activity in PDAC cells abrogated the impact of CAFs on clonogenic growth. Conclusion: Therefore, CAFs enhance PDAC clonogenic growth, self-renewal, and the frequency of CSCs through type I collagen production that enhances integrin-FAK signaling in PDAC cells. Abstract : Supplemental digital content is available in the text.